Graphite oxide as a support for palladium and rhodium complexes, assessed as catalysts for the partial hydrogenation of 1-heptyne - Liprandi, Domingo Antonio (2020)
Graphite oxide (GO) was used to anchor [PdCl2(TDA)2] and [RhCl(TDA)3] (TDA = NH2(CH2)12CH3) with 2wt % of metal load. Elemental analysis (EA), FTIR, XPS, XRD and atomic absorption spectroscopy (AA) were the techniques employed for characterization. FTIR and XRD revealed that both complexes were mainly immobilized on the GO surface. The partial hydrogenation of 1-heptyne was the test reaction to evaluate the catalytic behavior of these heterogenized complexes under mild conditions of temperature and pressure in a semi continuous process. The results were compared with those obtained with the Wilkinson catalyst under the same operational conditions. AA analysis revealed that there is no leaching of the complexes during the heterogeneous catalytic evaluations. [RhCl(TDA)3]/GO was the best catalyst due to electronic and steric effects as well as the influence of the support.